2004
DOI: 10.1017/cbo9780511607097
|View full text |Cite
|
Sign up to set email alerts
|

Church, State and Civil Society

Abstract: At a time when secular liberalism is in crisis and when the civic contribution of religion is being re-assessed, the rich tradition of Christian political theology demands renewed attention. This book, based on the 2001 Bampton Lectures, explores the relationship of the church both to the state and civil institutions. Arguing that theological approaches to the state were often situated within the context of Christendom and are therefore outmoded, the author claims that a more differentiated approach can be dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A review of the literature has revealed that in many cases, numerous church-state relation studies have concentrated on analysing which of the two institutions controlled the other at any given time in history and context (Sturzo 1962). Nevertheless, recent theological interest has shifted from analysis of church-state relations in terms of a diarchy (Sturzo 1962) -that is, which one controlled or was more powerful than the other -to how the Church, specifically, as part of the civil society should relate to the institutions of the wider community, culture, and government (Fergusson 2004;and Cooper 2007).…”
Section: The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature has revealed that in many cases, numerous church-state relation studies have concentrated on analysing which of the two institutions controlled the other at any given time in history and context (Sturzo 1962). Nevertheless, recent theological interest has shifted from analysis of church-state relations in terms of a diarchy (Sturzo 1962) -that is, which one controlled or was more powerful than the other -to how the Church, specifically, as part of the civil society should relate to the institutions of the wider community, culture, and government (Fergusson 2004;and Cooper 2007).…”
Section: The Problemmentioning
confidence: 99%
“…There is a need to look at Church and state relations in a newer light in the contemporary post-Christendom and post-modern era. One of the foremost thinkers in this novel way of evaluating Church-state relations is Fergusson's (2004) "Differentiated Model".…”
Section: The Differentiated Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…"The alignment of churches with nationalist movements can produce deplorable consequences." 71 Christians are first and foremost citizens in the body of Christ that exceeds the borders of the state. Still, "the new communal identity determined the character of its members and called for their highest loyalty .…”
Section: From the Gospel Toward The Common Goodmentioning
confidence: 99%
“…These differences lead Fergusson to construe Christian citizenship in nation states as "subordinated or stratified," not as alien. 73 Fergusson develops an account of Christian public engagement through civil society that moves from the gospel toward the common good. The church's mission in the world is to witness to Christ, and this witness extends outward in the pursuit of justice, peace, and charity.…”
Section: From the Gospel Toward The Common Goodmentioning
confidence: 99%